Perception of Quality of Life and its Components among Russian Students – Implications for Academic Teaching - Gawlik, Remigiusz; Titarenko, Roman; Titov, Sergei (Horyzonty Polityki, 2015)
The paper has 3 objectives: (i) identify QoL determinants of Russian Students; (ii) assess their relevance for decision-making when choosing life strategies; (iii) recognize their implications for academic teaching. The research sample were students from two Russian Universities. The study employed: literature analysis; exploratory research (direct individual in-depth interviews, survey based on a self-administered, web-based questionnaire with single-answer, limited choice qualitative & quantitative questions and gradings based on the Likert-type scale); explanatory research (informal moderated group discussions). The research findings show the relatively high significance of finance, career,stability, family, free time and other non-material QoL determinants. Research analysis reveals an inconsistency between respondents’ expectations and their work-life balance, which imposes a question about decision-making criteria at an early stage of career planning and the role of tertiary education in this process. Implications & Recommendations: (i) multicriteri decision-making processes, such as career planning, should comprise worklife balance; therefore both material and non-material QoL determinants should be incorporated into the analysis; (ii) as the role of Universities, beside educating, is also to guide and shape characters, Academia seems to be the right place for this task; (iii) therefore Universities should promote conscious lecturers as assistants to the process of identification of individual QoL determinants by their students. Contribution & Value Added: the research provides a fresh and improved perspective on quality of life and its determinants; it includes non-material QoL components and therefore brings qualitative determinants into economic research; it will provide data future comparisons; it comes from a research network linking European and Russian tertiary education institutions and University lecturers with intercultural teaching experience.